Imperial designs : war, humiliation & the making of history - Tripathi, Deepak (Potomac Books, 2013)
Since the age of Alexander the Great, waves of foreign armies have invaded the Middle East and South Asia to plunder their vast treasures. In Imperial Designs, Deepak Tripathi offers a powerful and unique analysis of how this volatile region has endured the manipulation and humiliation of war, especially since World War I and the fall of the Ottoman Empire. He argues that these foreign invasions and the consequent ignominy of the defeated peoples of the regions have had far reaching consequences. Over the centuries, again and again, the conquered peoples have been left helpless, their shame o.